The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/imds-07-2021-0416
|View full text |Cite
|
Sign up to set email alerts
|

Physical Internet deployment in industry: literature review and research opportunities

Abstract: PurposeThe Physical Internet (PI) provides solutions to improve the current unsustainable economically logistics systems. This paper aims to identify the key themes and point out the gaps to demonstrate the current state of the PI deployment in the industry. Furthermore, this paper attempts to provide possible opportunities for future research to lead research directions of PI deployment in the industry.Design/methodology/approachThis paper follows the methodology of systematic literature review (SLR) includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…For example, Björklund and Forslund (2018) believed that the sustainable development of the logistics industry requires innovative thinking. Through a literature review, Chen et al. (2022) showed the current situation of the physical Internet of things and provided solutions to improve the current unsustainable economic logistics system.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Björklund and Forslund (2018) believed that the sustainable development of the logistics industry requires innovative thinking. Through a literature review, Chen et al. (2022) showed the current situation of the physical Internet of things and provided solutions to improve the current unsustainable economic logistics system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Bj€ orklund and Forslund (2018) believed that the sustainable development of the logistics industry requires innovative thinking. Through a literature review, Chen et al (2022) showed the current situation of the physical Internet of things and provided solutions to improve the current unsustainable economic logistics system. Meanwhile, Luo et al (2022) proposed a new urban logistics solution through the physical Internet, designed a warehouse-type operation mode, provided flexible storage and transit solutions and argued that physical Internet urban logistics has more advantages than conventional solutions.…”
Section: Logistics Operations and Freight Platforms Enabled By Digita...mentioning
confidence: 99%
“…The vision of Physical Internet (PI) has gone through a strong maturing process since its conception (Montreuil, 2011), both in terms of its practical articulation and scientific grounding. Recent reviews of the PI-literature (Treiblmaier et al, 2020;Pan et al, 2021;Chen et al, 2022;Nguyen et al, 2022;Cortés-Murcia et al, 2022) explicitly link the PI system concepts to its founding disciplines: industrial engineering (IE) and supply chain management (SCM). Together these PI innovation agendas have helped to involve IE and SCM researchers outside the PI community and have promoted the bundling of global R&D efforts into converging streams of work.…”
mentioning
confidence: 99%